Effects of gum-based coatings combined with ultrasonic pretreatment before drying on quality of sour cherries - Fakhreddin Salehi; Moein Inanloodoghouz (Ultrasonics Sonochemistry, 2023)
Application of pretreatment methods such as ultrasound and edible coatings is used to reduce processing time and/or preserve food product quality in drying technology. The aim of this research was to measure the impacts of gum-based coatings (guar, sodium alginate, and basil seed gums) in combination with sonication before drying on total phenolic content (TPC), antioxidant capacity (AC), effective water diffusivity (Deff), total color difference (ΔE), surface shrinkage (SS), and rehydration ratio (RR) of sour cherries. Ultrasonic pretreatment (40 kHz, 150 W, at 25 °C, for 12 min) increased the TPC, AC, Deff, and RR, and decreased the drying time, ΔE, and SS values of sour cherries. Edible coating increased the TPC, AC, drying time, and RR, and decreased the Deff, ΔE, and SS values of sonicated sour cherries. The TPC for untreated, uncoated-sonicated, guar gum-coated, sodium alginate-coated, and basil seed gum-coated sour cherries were 2965.9, 3398.1, 3480.8, 3511.0, and 3898.3 Âµg gallic acid equivalent/g dry, respectively. The highest value of AC (71.2±3.7 %) was observed on coated sour cherries by basil seed gum. The experimental data for drying curves were fitted to several widely used models, and the Midilli model using the experimental constants that best represent the drying rate of sour cherries. The edible coatings significantly reduced the color changes and shrinkage of dried sour cherries, with the lowest ΔE and SS values in the basil seed gum-coated samples (p < 0.05).